GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 94036 species occurrences available in GBIF matching the query: TaxonKey: 95 BasisOfRecord: Living Specimen. The dataset includes 94036 records from 21 constituent datasets: 1159 records from Vietnam Type Culture Collection. 1 records from Culture Collection of Cryophilic Algae. 3 records from Coimbra Collection of Algae. 86 records from Mushroom Collection in BCRC. 3858 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 27787 records from CBS fungi strains. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 7576 records from Genebank, National Institute of Agrobiological Sciences. 1615 records from Yeast Collection in BCRC. 14583 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 5053 records from Database Schema for UC Davis [Phaff]. 7250 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 2267 records from Fungi Collection in BCRC. 4 records from SysTax - Botanical Gardens. 567 records from Collection of Industrial Microorganisms. 224 records from Micoteca da Universidade do Minho. 1 records from Culture Collection of Algae. 17526 records from CABI Bioscience Genetic Resource Collection. 3 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 1443 records from DSMZ Collection of Filamentous Fungi and Yeasts. 3029 records from Japan Collection of Microorganisms, RIKEN BioResource Center.
Keywords: GBIF; biodiversity; species occurrences